Primary Prebiotic Properties of Ethanolic Sugar Extract from Mung Bean Seeds - Wongputtisin, Pairote; Lahsom, Narin (Journal of Food Technology, Siam University, 2018)
Leguminous seeds are source of raffinose family oligosaccharides which have been accepted as an effective prebiotic substance. In this study, low molecular weight sugars were extracted from 4 cultivars of mung bean seed, i.e. Kampangsan1, Kampangsan2, Chainat36 and Chainat72, using 50% (v/v) ethanol. Subsequently, composition and amount of extracted sugar and their capacity in growth stimulation of some enteric bacteria were investigated. The results showed that the average size of sugars in term of degree of polymerization were 3-7. The cultivar Kampangsan2, Chainat36 and Chinat72 contained high amount of raffinose at 1.76-2.29 mg/g dry seed, stachyose at 33.95-34.82 mg/g dry seed and verbascose at 13.59-20.31 mg/g dry seed. Growth of Lactobacillus acidophilus TISTR1338, L. plantarum TISTR541 and L. lactis TISTR1464 were significantly stimulated by these sugars (p<0.05), while that of Salmonella enterica serovar Typhimurium TISTR292 and Escherichia coli were not stimulated. Moreover, growth of S. Typhimurium could be suppressed when was co-cultured with those 3 strains of Lactobacillus sp. in media contained extracted sugar from mung beans as a carbon source. Thus, it might be concluded that ethanolic sugar extracted from 4 cultivars of mung bean could exhibit the primary properties of prebiotic substance.